Citing of Industry Standards in Scholarly Publications - Erin M Rowley; A Ben Wagner (Issues in Science and Technology Librarianship, 2019)
Industry standards are used in many disciplines, including science and technology areas. To date, little research has been conducted regarding the citing of standards in scholarly publications. The aim of this study was to answer two questions: Are standards being cited in scholarly publications? And, if so, what are the characteristics of the publications citing standards? We postulated that the answer to these questions would be of use to science and engineering librarians for collection development and research assistance purposes. A cited reference search was conducted using Web of Science Core Collection™ (WOSCC) to determine if standards are cited. Our research focused on three major standards organizations: ASTM International, the International Organization of Standardization (ISO), and the European Committee for Standardization (CEN). The study was limited to publications published from 2015-2017. The results confirmed our hypothesis that standards are cited in scholarly publications in science and technology fields. In addition, we discovered that standards were cited in publications from nearly 100 countries. Funding agency and institutional affiliation were also analyzed. The data from the study confirmed the international reach and broad utility of standards in a wide range of disciplines.